SOSIALISASI PENDIDIKAN KEWIRAUSAHAAN DI ERA GLOBALISASI DI DESA BATANG NADENGGAN DUSUN SUNGAI BONDAR KEC. SUNGAI KANAN, LABUHAN BATU SELATAN - Rizki Syahputra, Nova Jayanti Harahap, Elvina, Pitriyani, Zufrie (PT.JNDI, JURNAL BIMA, 2024)
Entrepreneurship education is very important for teachers' capital. where with advances in technology and changing times, teachers must be able to own or be able to be independent through entrepreneurship. This service is carried out using lecture and question and answer methods. It is hoped that the results of this service can have a positive impact on teachers in the Batang Nadenggan village environment, Sungai Bondar sub-district. Right river, south rock harbor.